Implementation Of Cooperative Problem–Based Learning In Achieving Learning Outcomes - Mohamad Juoi, Jariah; Mohd Rosli, Zulkifli; Chang, Siang Yee; Shamsuri, Siti Rahmah; Rahim, T.A (2011)
Material Selection is one of the program core subjects introduced in Bachelor of Engineering in Manufacturing Engineering. Five learning outcomes have been outlined in the subject. In order to achieve the learning outcomes, the subject delivery involves implementing Cooperative Problem-Based Learning (CPBL) activities as a part of teaching and learning process. Generally, the summative assessment involves cognitive domain and soft skill. This is an improved approach in teaching and learning process as compared to the common practice. For each learning outcome, a specific learning domain and taxonomy level were defined and rubrics for assessment were developed accordingly. Constructive alignment among the learning outcomes, delivery methods, assessment and evaluation gives an overall reflection on the students’ Iearning outcomes attainment. Students' ac1tievement is evaluated based on Key Performance Index set by the Faculty. Students' reflection in the subject matters and teaching and learning process provides essential inputs in outlining a few strategies for Continuous Quality lmprovement purpose. It was observed that Cooperative Problem-Based Learning activities arc able to promote student-centered learning culture among the students. It also nurtures students to be graduates who fulfill the criteria outlined in the Program Outcomes.